The intervening impact of mas effectiveness on the relationship between contingent variables and organization performance: a study of Libyan banking and petroleum organizations / Naser Bashir A Ghanem - A Ghanem, Naser Bashir (2016)
This study is undertaken with the purpose of examining the relationship between management accounting system effectiveness (MASE) and organization performance (OP). Specifically the research seeks to figure out what are the benefits derived from MAS that OP could have from what expected to be the main influences in MASE. Moreover, the research concentrates on MASE that resulted from contingent factors, organizational coordination and control requirements (OCCR) and information quality IQ. In particular, examine the effect of MASE arising from OCCR and IQ on OP with regard to individual impact (INIM) in developing countries' concept, the case of Libya. More specifically, IQ as one of the MAS requirement and OCCR which consist of information interdependence (INFIN), formalization (FO) and information inter-organization (INFORG) are the selected contingent variables, with MASE modelled as intervening mechanism between these contingent variables, and OP. This study also looks for evidences about the effectiveness of suitability of MAS' information from system users' perspective (perceptions of MAS's end users such as CEOs). Previous researchers have realized the contribution of information technology (IT) in improving the individual performance chiefly in terms of productivity and effectiveness (Iivari, 2005a). The study is beneficial and significant because it supports the need to consider individual and environmental factors together. The expected outcome of the research is that MASE that rose from the impact of the contingent variables has a direct positive impact on OP. Also the relation between system effectiveness and performance may effected by INIM. In addition, using users who work in companies that are working in a developing country, Libya, and have adopted sophisticated systems, those systems help exchange information between departments and other companies electronically as the population of this study is a useful for this research because of the fundamental changes that Libyan economic have especially after the lifting of the embargo on Libya which took place April 1999 when the UN Security Council had suspended the sanctions imposed on Libya and by 2003 the sanctions was terminated. This change has created a good environment for researchers to conduct studies because, recently, some of the current organizations have adopted advanced systems such as communication, banking and oil and gas companies (Twati, 2008, Leftesi, 2008), and hence the existence of the knowledge that individuals gained to evaluate these systems after they have got practical experience in both advanced and traditional systems. A quantitative approach was chosen for this study using items from previous studies. The result shows significant mediating effect of MAS effectiveness on the relationship between the chosen contingent variables and organization performance and the comprehensive measurement contributed in this study shows a satisfied result. However individual impact shows weak moderating impact and the end user satisfaction and MAS usefulness show different impact on organization performance. In conclusion, this study is seeking to develop the above by relaying on an existent established knowledge of the literature that studied both AIS and MAS's variables (contingency perspective) and tools (Nicolaou, 2000, Chenhall and Morris, 1986, Rom and Rohde, 2007) and the contribution of this study was clearly recognised.